2021
DOI: 10.1021/acs.est.0c07545
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Fate Modeling of Nanoplastics in a Salinity Gradient Using a Lab-on-a-Chip: Where Does the Nanoscale Fraction of Plastic Debris Accumulate?

Abstract: The aim of this study is to demonstrate how the flow and diffusion of nanoplastics through a salinity gradient, as observed in mangrove swamps, influence their aggregation pathways. These two parameters have never yet been used to evaluate the fate and behavior of colloids in the environment, since they cannot be incorporated into classical experimental setups. Landsea continuums, such as estuaries and mangrove swamp systems, are known to be environmentally reactive interfaces that influence the colloidal dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…Traditional theory has well established that the aggregation of nanoparticles is significantly influenced by the ionic strength of the solution. Gigault et al recently investigated the aggregation behavior of nC 60 under a gradient of ionic strength in a microfluidic device (Figure B). , Contrary to the classical notion that nanoparticles would aggregate under high salinity, the existence of a gradient was found to enhance the stability of nanoparticles, and a fractionation phenomenon was observed. A substantial portion of the nanoparticles would aggregate to microscale, while a smaller portion remained stable and maintained mobility .…”
Section: Microfluidics For Investigating Soil Interfacial Processesmentioning
confidence: 95%
See 2 more Smart Citations
“…Traditional theory has well established that the aggregation of nanoparticles is significantly influenced by the ionic strength of the solution. Gigault et al recently investigated the aggregation behavior of nC 60 under a gradient of ionic strength in a microfluidic device (Figure B). , Contrary to the classical notion that nanoparticles would aggregate under high salinity, the existence of a gradient was found to enhance the stability of nanoparticles, and a fractionation phenomenon was observed. A substantial portion of the nanoparticles would aggregate to microscale, while a smaller portion remained stable and maintained mobility .…”
Section: Microfluidics For Investigating Soil Interfacial Processesmentioning
confidence: 95%
“…Gigault et al recently investigated the aggregation behavior of nC 60 under a gradient of ionic strength in a microfluidic device (Figure B). , Contrary to the classical notion that nanoparticles would aggregate under high salinity, the existence of a gradient was found to enhance the stability of nanoparticles, and a fractionation phenomenon was observed. A substantial portion of the nanoparticles would aggregate to microscale, while a smaller portion remained stable and maintained mobility . This work suggests that evaluating the fate of nanoparticles should account for the heterogeneity of the environments, which is largely ignored in previous studies.…”
Section: Microfluidics For Investigating Soil Interfacial Processesmentioning
confidence: 95%
See 1 more Smart Citation
“…NPLs have been recently recognized as one of the least studied types of marine liter but potentially one of the most hazardous. , Thus, information on the chemical composition (including polymer type, additives and sorbed contaminants), number concentrations, size/size distribution and mass of NPL particles as well as on their shapes and surface properties are essential for the understanding of NPL impacts on the environment and human health. Furthermore, the knowledge on the formation and (bio)­degradation of NPL particles, on their colloidal behavior and heteroaggregation with inorganic colloids and natural organic matter (NOM) in the environment will help to understand the sources, transport and fate of this challenging particulate analyte. ,, It is worth mentioning that the influence of the NOM on NMPs fate, effects and detectability strongly depends on the particle size. The NOM is a minor component compared with the host plastic at the microscale.…”
Section: Chemical Analysis Of Nanoplasticsmentioning
confidence: 99%
“…Their surface functionalization was a priori chosen 21 as no characterization of nanoplastic surface functional groups is available. Finally, recent studies have demonstrated that the size and shape influence nanoplastic retention in porous media and their stability in aqueous systems 26,27 .…”
Section: Introductionmentioning
confidence: 99%